Pendekatan E-Learning sebagai Media Dakwah Islam - Surya Eka Priyatna (UIN Antasari Banjarmasin, 2017)
Objective approach to e-learning as a medium for Islamic dakwah is to provide an alternative method of dakwah with a wider coverage area and update rapid delivery of content. Dakwah by e-learning media should have the maturity level of a good design of overall message to achieve global success. Dakwah material as the main content should touch the daily life problems faced by the community, and offer solution based on the guidance and instruction of Islam